THE INFLUENCE OF GEOLOGICAL CONDITIONS ON THE FORMATION OF THE COLOR OF PRECIOUS STONES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The color of gemstones is formed by a complex interaction of chemical composition, crystal chemistry, and the geological conditions of their formation. Trace elements, lattice defects, and structural features of minerals depend on temperature, pressure, the redox environment, and the composition of the fluids in the rocks where crystal formation occurred. This article examines the main color mechanisms: electron transitions in transition metals, interionic charge transitions, radiation-induced defects, and structural interference effects. Using corundum (ruby and sapphire), beryl (emerald), and topaz as examples, the role of the geochemical environment in the formation of their characteristic colors is demonstrated.